2005
DOI: 10.1095/biolreprod.105.040881
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of Caveolin 1 by Oxidative Stress Is Reversible and Dependent on the c-src Tyrosine Kinase but Not Mitogen-Activated Protein Kinase Pathways in Placental Artery Endothelial Cells1

Abstract: Acute H(2)O(2) exposure to placental artery endothelial cells induced an array of tyrosine-phosphorylated proteins, including caveolin 1 (CAV1) rapid and transient tyr(14) phosphorylated in a time- and concentration-dependent manner. Basal tyr(14) phosphorylated CAV1 was primarily located at the edges of cells and associated with actin filaments. Phosphorylated CAV1 was markedly increased and diffused with the disorganization of actin filaments at 20 min, disappeared at 120 min treatment with 0.2 mM H(2)O(2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 57 publications
2
34
1
1
Order By: Relevance
“…38 Our results show that liver regeneration after PH causes some Cav-1 phosphorylation, and the phosphorylated protein is located in cytosolic domains.…”
Section: Discussionmentioning
confidence: 57%
“…38 Our results show that liver regeneration after PH causes some Cav-1 phosphorylation, and the phosphorylated protein is located in cytosolic domains.…”
Section: Discussionmentioning
confidence: 57%
“…The relationship of caveolin-1 with oxidative stress can also be viewed from another point of view. Recent studies have demonstrated that caveolin-1 is a target molecule in p38 MAPK mediated response to stress conditions such as oxidative stress (27,28). After such stimuli, caveolin-1 is phosphorylated and thus contributes to various signalling pathways (60) resulting most likely in processes, such as premature cellular senescence (27).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in protein function lead to the lapse of cell functions (adhesion) and cell mobility and the development of metastatic processes (22). Furthermore, it has been demonstrated that caveolin-1 expression is induced under stress conditions, such as oxidative stress (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the Src-kinase family can phosphorylate TRPC3 (Kawasaki et al, 2006) and TRPC6 (Hisatsune et al, 2004); however, regulation of TRPC1 activity by Src has not been investigated. Src kinase has been shown to be activated by reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ) (Chen et al, 2005), and TRPC3 activity is increased by ROS (Poteser et al, 2006). Thus, it is possible that ROS-induced Src activation, leads to phosphorylation and activation of transient receptor potential canonical (TRPC) channels.…”
Section: Introductionmentioning
confidence: 99%